2022
DOI: 10.1139/bcb-2021-0322
|View full text |Cite
|
Sign up to set email alerts
|

SET8, a novel regulator to ameliorate vascular calcification via activating PI3K/Akt mediated anti-apoptotic effects

Abstract: Previous studies have showed that the apoptosis of vascular smooth muscle cells (VSMCs) underlies the mechanism of pathological calcifications in patients with chronic kidney disease (CKD). SET domain-containing protein 8 (SET8), as an efficient protein has been reported to modulate cell apoptosis in hepatocellular carcinoma cell, esophageal squamous cell and neuronal cell through regulating pathological processes, such as cell-cycle progression and transcription regulation. However, whether SET8 is involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…After acclimatization, rats were randomly divided into two groups (n = 10): namely control group and VC group. Rat model of VC was constructed by 5/6 nephrectomy combined with a high phosphate diet protocol as previously described [33]. Brie y, rst, rats were anesthetized and underwent a 2/3 left nephrectomy.…”
Section: Animals and Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…After acclimatization, rats were randomly divided into two groups (n = 10): namely control group and VC group. Rat model of VC was constructed by 5/6 nephrectomy combined with a high phosphate diet protocol as previously described [33]. Brie y, rst, rats were anesthetized and underwent a 2/3 left nephrectomy.…”
Section: Animals and Groupsmentioning
confidence: 99%
“…Isolation of VSMCs was performed from the aortas of Sprague-Dawley rats (8-weeks old) with the use of the explant method as described in a previous study [33]. After cultured in Dulbecco's Modi ed Eagle Medium containing 10% fetal bovine serum, cells were incubated at 37° C in humidi ed 5% CO2.…”
Section: Cell Culturementioning
confidence: 99%
“…Furthermore, recent evidence indicated that apoptosis is a significant process in the onset of VC, which is usually observed before the formation of calcified nodules in VSMCs 20 . Apoptotic bodies derived from VSMCs might act as nucleating structures for calcium‐phosphate crystals deposited in the vascular wall, finally activating the procedure of VC 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent evidence indicated that apoptosis is a significant process in the onset of VC, which is usually observed before the formation of calcified nodules in VSMCs. 20 Apoptotic bodies derived from VSMCs might act as nucleating structures for calcium-phosphate crystals deposited in the vascular wall, finally activating the procedure of VC. 21 Moreover, ERS was proved to be one of the upstream of apoptosis in various pathogenesis, such as diabetes mellitus, atherosclerosis, 22 and chronic kidney disease, 23 all of which are associated with VC in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Although SET8 has a complex mechanism of action in H4K20 and non-histone catalysis, in terms of overall effect SET8 is significantly downregulated in the calcification model ( 114 ). The methylation modification of H4K20 is highly complex due to the different effects at different levels of methylation; therefore, researchers may focus on the specific role of SET8 in different pathways and the effects of other H4K20 methyltransferases on VC.…”
Section: Hkmts Substrates Lysine From Histone To Control Vcmentioning
confidence: 99%